FACTORS ASSOCIATED WITH ADHERENCE TO ANTIHYPERTENSIVES AMONG HYPERTENSIVE PATIENTS ATTENDING HYPERTENSIVE CLINIC OF MBALE REGIONAL REFERRAL HOSPITAL MBALE DISTRICT. A CROSS-SECTIONAL STUDY . - ALIRO, MERCY; Namutebi, Florence (Student's Journal of Health Research Africa, 2023)
Background: Adherence to antihypertensive medication is a major challenge today, this study was meant to determine the factors associated with adherence to AHM. The study was to assess the socioeconomic factors, identify the Demographic factors, to determine the Health system-related factors affecting adherence to antihypertensive drugs among hypertensive patients attending Mbale Regional Referral Hospital Mbale district. Methodology: The research design was a cross-sectional study where quantitative approaches were used, the sample size was 97 patients, and was determined using Kish and Leslie formula. The sampling method used was random sampling. Data were analyzed using pencils, pens, and a calculator and then presented using figures, tables, and pie charts. Findings: Most of the respondents 42(43.3%) said that they spent more than ugshs10,000 to purchase anti-hypertensive medications per week, 48 (48.5%) respondents said that they spent above ugshs 5000 for transport to the health facility every hypertensive clinic day. The majority of the respondents 55(56.7%) said that their families reminded them when to take their medications, 72 (74.2%) said that they did not receive all their medications from MRRH. 34 (47.2%) of the respondents said that most of the medications prescribed to them were not always available at the facility. Conclusions: The study revealed that the patient’s economic status and family support played a vital role in ensuring adherence to AHM, it also revealed that the absence of the prescribed medication and the patient’s inability to access the hospital for reviews was a major hindrance to adherence Recommendations: From the study, the researcher recommends that the hospital should put up support groups and ensure continuous education of the patients on the importance of adherence to hypertensive medication and the consequences of non-adherence. The government and its partners should always ensure the timely supply of antihypertensive medicines to the health facility.